Upaya Meningkatkan Hasil Belajar Gerak Dasar Lompat Jauh Gaya Menggantung dengan Menggunakan Alat Bantu Kotak Kardus - Martinus Handoko Prastowo (Syntax Idea, 2021)
The purpose of this research is to improve the achievements of long jump hanging style sports through the use of cardboard box aids, learning in grade VI students of SDN Kanung 02 sawahan subdistrict madiun in the 2019/2020 school year. This research uses Class Action Research (PTK) method. The data analysis techniques used are descriptive quantitative. The research procedure is to determine the steps in carrying out the research. The steps of implementation of PTK procedurally is carried out participatory or collaboration (teachers, other PJOK) in collaboration, starting from the orientation stage followed by the preparation of action plans followed by the implementation of actions in cycle I, analytical discussions that are then continued to the reflection-evaluative steps of activities carried out in cycle I, to then prepare a plan of modification, correction, or correction, or improvement in cycle II and so on. The results showed that by using learning aids can improve the results of learning basic motion long jump style hanging from pre cycle to cycle I and from cycle I to cycle II. The result of long jump learning style hanging on pre cycle in the complete category is 33.3% or 6 students, at the end of cycle I after being given learning basic motion techniques long jump hanging style using cardboard aids increased to 55.55% or 10 students, then again there was an increase after being given action in cycle II to 88.88% or 16 students with more emphasis on increasing the chances of students in doing the long jump movement overall. The conclusion of this study is that the use of learning aids can improve the results of learning the basic motion of long jump hanging style in grade VI students of SDN Kanung 02 in the 2019/2020 school year.